1995
DOI: 10.1177/096368979500400109
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Viability of Isolated Bovine Adrenal Medullary Chromaffin Cells following Intrastriatal Transplantation

Abstract: Adrenal medullary grafts generally exhibit poor viability when grafted into the striatum. Previous work in our laboratory demonstrated that chromaffin cells can survive well for up to 2 mo following grafting into the intact rat striatum after cells are isolated from the nonchromaffin supporting cells (fibroblasts and endothelial cells) of the adrenal medulla. The aim of the present study was to assess the long-term viability of isolated bovine chromaffin cells following grafting into the intact rat striatum. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…However, the transplant was subjected to an intense inflammatory reaction at the time of perfusion, and we assume that this graft eventu ally would have succumbed to rejection if the study had not been terminated. Long-term survival of discordantxenogeneic grafts without immunosuppression has been observed before(5,17,46) and stresses the unique immu-nological properties of the brain, rendering it a specifi cally suitable site for xenogeneic cell transplantation.Immune Response to the Porcine GraftsTheimmunosuppressive treatment used in this study was not sufficient to enable stable graft survival and per sistent functional effects in all recipients. In four immu nosuppressed animals, a strong immunological rejection was ongoing at the time of perfusion.…”
mentioning
confidence: 84%
“…However, the transplant was subjected to an intense inflammatory reaction at the time of perfusion, and we assume that this graft eventu ally would have succumbed to rejection if the study had not been terminated. Long-term survival of discordantxenogeneic grafts without immunosuppression has been observed before(5,17,46) and stresses the unique immu-nological properties of the brain, rendering it a specifi cally suitable site for xenogeneic cell transplantation.Immune Response to the Porcine GraftsTheimmunosuppressive treatment used in this study was not sufficient to enable stable graft survival and per sistent functional effects in all recipients. In four immu nosuppressed animals, a strong immunological rejection was ongoing at the time of perfusion.…”
mentioning
confidence: 84%
“…This may have been due to the high degree of viability and purity of the BCCs used in the study. Czech et al (26) and Schueler et al (27) found that the nonchromaffin supporting cells (fibroblasts and endothelial cells) of the adrenal medulla can induce strong immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Cell isolation and encapsulation procedure. Chromaffin cells were isolated from bovine adrenal medullary tissue by conventional methods [11] and purified using the differential plating method [12]. The purified chromaffin cells, with 1.4% alginate (Sigma, USA), were dropped into a calcium chloride bath and coated with 0.05% poly-L-Lysine and 0.2% alginate in turn.…”
Section: Methodsmentioning
confidence: 99%